PaKRP, a cyclin-dependent kinase inhibitor from avocado, may facilitate exit from the cell cycle during fruit growth - Sabag, Michal (Plant science : an international journal of experimental plant biology, 2013)
Copyright © 2013 Elsevier Ireland Ltd. All rights reserved.